2014
DOI: 10.4161/auto.28615
|View full text |Cite
|
Sign up to set email alerts
|

BECN1 is involved in the initiation of mitophagy

Abstract: The autophagy protein BECN1/Beclin 1 is known to play a central role in autophagosome formation and maturation. The results presented here demonstrate that BECN1 interacts with the Parkinson disease-related protein PARK2. This interaction does not require PARK2 translocation to mitochondria and occurs mostly in cytosol. However, our results suggest that BECN1 is involved in PARK2 translocation to mitochondria because loss of BECN1 inhibits CCCP- or PINK1 overexpression-induced PARK2 translocation. Our results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 45 publications
6
55
0
Order By: Relevance
“…Beclin-1, central to the regulation of autophagy, is involved in the formation of autophagosomes via membrane recruitment [23]. LC3 is another important molecule for autophagy as a constituent of the autophagosome membrane [24].…”
Section: Discussionmentioning
confidence: 99%
“…Beclin-1, central to the regulation of autophagy, is involved in the formation of autophagosomes via membrane recruitment [23]. LC3 is another important molecule for autophagy as a constituent of the autophagosome membrane [24].…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids expressing scrambled shRNA or shRNAs against mouse RHOT1 (KM35868N, suppresses efficiently also rat RHOT1), rat RHOT2 (KR44228N) and rat PINK1 (KR55105N) were from SABiosciences and validated earlier (Cagalinec et al , ; Choubey et al , ). Plasmids expressing mitochondrial DsRed2 (632421), mitochondrial CFP (632432) and EGFP (6085‐1) were from Clontech, untagged Miro2 (SC127208) from Origene and mKate2‐mito (FP187) from Evrogen.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have suggested a variety of roles for Ambra1 including: (1) interaction with parkin during mitochondrial depolarization, whereupon Ambra1 activates class III PI3K (Van Humbeeck et al, 2011); (2) Ambra1 mediated mitochondrial depolarization and subsequent ubiquitination by parkin; (3) induction of parkin-independent mitophagy; and (4) binding of LC3 to complete autophagophore formation (Strappazzon et al, 2015). Beclin-1 has been shown to bind to both PINK1 and parkin to promote mitophagy and parkin translocation (Choubey et al, 2014). Because of their importance in mitophagy initiation, inducing Ambra1 and Beclin-1 translocation to the mitochondria and/or enhancing their function has the potential to enhance parkin-dependent and -independent mitophagy, thereby enabling the clearance of damaged mitochondria.…”
Section: Therapeuticsmentioning
confidence: 99%